HOUSEHOLD CONSUMPTION ADJUSTMENT AND ECONOMIC STRATEGIES AMID RISING BASIC COMMODITY PRICES - Nurbuana Amir; Nurtasyani Yusni; Andi Fauziah Machmud (Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study aims to analyze household strategies in determining spending priorities amid rising basic commodity prices in Bone Regency. The research examines the impact of price increases on household expenditure patterns, the strategies adopted to manage expenses, and the role of government programs and Islamic economic values in supporting household financial decisions. This study employed a qualitative method with a descriptive approach through interviews with households affected by the increase in basic commodity prices. The findings show that rising prices have increased household expenditures, reduced purchasing power, and shifted spending priorities toward essential needs, particularly food, children’s needs, education, and business-related necessities for households operating small enterprises. To address these challenges, households implemented various strategies, including preparing shopping lists, comparing prices, utilizing discounts and promotions, reducing non-essential expenditures, avoiding consumptive behavior, and choosing more affordable alternatives. Government programs, particularly subsidized markets, were perceived as helpful in easing financial burdens despite certain limitations in implementation. From the perspective of Islamic economics, households demonstrated prudent consumption behavior by prioritizing needs over wants, avoiding wastefulness (israf), practicing moderation, and allocating part of their income for emergency needs. The study concludes that households in Bone Regency have adapted to rising prices through rational and planned financial management. Strengthening price stabilization policies and improving assistance programs are recommended to support household welfare.